THE FEATURES OF THE PEDAGOGICAL APPROACH TO THE STUDY OF LARGE FORMS IN THE WORKS OF M.P. MUSORGSKY AND N.A. RIMSKY-KORSAKOV - Okhunjon Kimsanov; Dilrabo Jalolitdinova (Bright Mind Publishing, 2025)
The study of large-scale musical forms plays a crucial role in the professional development of music students. The works of M. P. Mussorgsky and N. A. Rimsky-Korsakov represent unique examples of Russian musical heritage, demonstrating complex structural organization, thematic development, and innovative orchestration techniques. Their compositions, particularly operas, symphonic works, and orchestral suites, present challenges for performers and music educators due to their unconventional harmonic language and dramatic expressiveness. Pedagogical approaches to studying these large forms require a deep analytical perspective, integration of historical and stylistic contexts, and practical performance techniques to enhance students' musical interpretation skills. In Uzbekistan, the inclusion of Mussorgsky’s and Rimsky-Korsakov’s compositions in academic curricula helps students develop a comprehensive understanding of musical form, orchestration, and expressive means. This article explores the pedagogical methodologies applied in teaching large-scale works of these composers, their impact on students' artistic perception, and strategies for effective incorporation into music education.
Keywords: Large-scale forms, M. P. Mussorgsky, N. A. Rimsky-Korsakov, musical interpretation, orchestration, thematic development, harmonic language, pedagogical approaches, music education, artistic perception.